Analisis Konseptual Pasar Uang, Pasar Barang, dan Keseimbangan Pasar - Fadilah, Khairul; Ananda, Lili Pernata; Albahi, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid growth of Islamic financial markets has brought significant attention to the dynamics of money markets, goods markets, and market equilibrium within the framework of Islamic economics. This study explores the interactions between these markets, focusing on the challenges and opportunities that arise in the application of Islamic principles in contemporary economies. The purpose of this study is to analyze how Islamic economic concepts, such as the regulation of money and goods markets and the distribution of wealth through Islamic financial instruments, can be applied to achieve market equilibrium. This qualitative study uses a desk-based research approach, analyzing literature and scholarly articles published from 2019 onwards to collect relevant data. The findings indicate that despite the growing potential of Islamic finance, significant barriers remain, including limited instruments in the money market, inconsistent halal certification processes, and challenges in wealth redistribution mechanisms. The study also highlights the potential role of technology, particularly blockchain, in increasing transparency and efficiency in these markets. The study concludes that with the right regulatory framework, increased technological integration, and stronger institutional coordination, Islamic economics can contribute significantly to achieving a more equitable and sustainable global economic system.